The Sarcastic Edge: How Impoliteness Strategies Construct Rhetorical Authority in the 7th IUDC Arabic Debate - Aditya Fitrah; Eva Lathifah Fauzia; Muhammad Ibnu Pamungkas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Debate requires individuals to think critically, systematically, and strategically when selecting linguistic devices to defend arguments, maintain social standing, and challenge opponents. This study aims to identify and explain the rhetorical functions of impoliteness strategies used in the context of high stakes competitive debate. Using a descriptive qualitative approach, this study analyzes data sourced from video documentation of the final round of the 7th IUDC Arabic Debate in 2024 in Qatar. The data were analyzed using content analysis techniques based on Culpeper’s framework of impoliteness. The results indicate the presence of all five impoliteness strategies: Bald on Record, Positive Impoliteness, Negative Impoliteness, Sarcasm, and Withhold Politeness, with sarcasm being the most dominant strategy. This dominance simultaneously undermines the opponent’s positive face while showcasing the speaker’s composure and analytical power before the judges. Each strategy was not chosen randomly but as a response to specific communicative demands, and the combination of their use by both finalist teams constitutes a face-management strategy inseparable from competitive success. This finding expands Culpeper’s framework of impoliteness by demonstrating that, in high stakes academic debates, impoliteness strategies function as cumulative rhetorical tools through which debaters establish their own authority, undermine their opponents’ credibility, and ultimately convince the judges of their team’s argumentative superiority.